Foreign aid and industrial development in Pakistan - Brecher, Irving; Abbas, S. A. (Cambridge, England : at the University Press, 1972)
The book examines the history of aid flows to Pakistan; their interaction with economic growth and planning in the country; the role of foreign aid in the balance of payments and external indebtedness; and the reciprocal links between aid on the one hand and income, employment, investment and the structure of Pakistani industry on the other.
Includes index.
Includes bibliographical references: p. 251-266.
lje 28/09/2018
Loans
Keywords: Economic assistance; Industries; Pakistan